Simulation of the evolution of floor covering ceramic tiles during the firing (2013)
In the context of the firing of ceramic tiles the problem of simulating the final shape of the body is relevant because several defects can occur and the tile can be rejected if the conditions of the firing are inadequate for the geometry and materials of the tile -- The existing literature on this problem indicates that previous works present limitations in aspects such as not using a model characteristic of ceramics at high temperatures and oversimplifying the problem -- As a response to such shortcomings, this article presents a simulation with a 3-dimensional Norton’s model, which overcomes the difficulties because it is characteristic of ceramics at high temperatures -- The results of our simulated experiments show advantages with respect to the identification of the mechanisms that contribute to the final shape of the body -- Our work is able to divide the history of temperatures in stages where the evolution of the thermal, elastic and creep deformations is simplified and meaningful -- That is achieved because our work found that curvature is the most descriptive parameter of the simulation, the most important contribution of this article -- Future work is to be realized in the creation of a model that takes into account that the shrinkage is dependent on the history of temperatures -- The main shortcoming of the paper is the lack of physical experiments to corroborate the simulations